Synthesis and Characterization of Azo Dye Para Red and New Derivatives - L. Abd-Alredha R. Al-Rubaie; R. Jameel Mhessn (E-Journal of Chemistry)
Azo dyes para red was synthesized. The products were characterized by FTIR and UV-Visible spectrophotometers. The antibacterial activities of the compounds were studied using gram positive and gram negative microorganism.